Black women, citizenship, and the making of modern Cuba - Brunson, Takkara K. (University of Florida Press, 2021)
"In the first book to focus on the activism of Black women during Cuba's prerevolutionary period, Takkara Brunson discusses how these women battled exclusion on multiple fronts but played an important role in forging a modern democracy"--